Nonequilibrium dynamics and thermodynamics provide the underlying physical mechanism of the perceptual rivalry - Yuxuan Wu; Liufang Xu; Jin Wang (Physical Review Research)
Perceptual rivalry, where conflicting sensory information leads to alternating perceptions crucial for associated cognitive function, has long attracted research attention. Despite progress being made, authors of recent studies have revealed limitations and inconsistencies in our understanding across various rivalry contexts. We develop a unified physical framework, where perception undergoes a consecutive phase transition process encompassing different multistate competitions. We reveal the underlying mechanisms of perceptual rivalry by identifying dominant switching paths among perceptual states and quantifying mean perceptual durations, switching frequencies, and proportions of different perceptions. We uncover the underlying nonequilibrium dynamics and thermodynamics by analyzing average nonequilibrium flux and entropy production rate, while associated time series irreversibility reflects the underlying nonequilibrium mechanism of perceptual rivalry and link thermodynamical results with neuroelectrophysiological experiments. Our framework provides a global and physical understanding of brain perception, which may go beyond cognitive science or psychology but embodies the connection with wider fields such as decision-making.